Aqueous synthesis of protectant-free copper nanocubes by a disproportionation reaction of Cu2O on synthetic saponite. Issue 61 (29th May 2018) - Miyagawa, Masaya; Usui, Miharu; Imura, Yu; Kuwahara, Shota; Sugai, Toshiki; Tanaka, Hideki
Abstract : Shape formation of Cu nanocubes by selective etching with a disproportionation reaction. Abstract : Here, we report a synthesis of Cu nanocubes by photoreduction of CuSO4 . Because synthetic saponite (one of the layered clay minerals) was used as the adsorbent, the nanocubes contained no capping agents or protectants, and the disproportionation reaction of Cu2 O with H2 SO4 was found to be the key for morphological control.